DFT study of co-doping effects on the electronic, optical, transport, and thermodynamic properties of (5,5) SWCNTs for photovoltaic and photonic applications - I.A. Tabet Djeudi; G.W. Ejuh; P.F. Bissi Nyandou; Oumaima Douass; A. Teyou Ngoupo; C.C. Fonkem; Y. Tadjouteu Assatse; R.A. Yossa Kamsi; J.M.B. Ndjaka; Bilel Mehnen (Chemical Physics Impact)
This study employed density functional theory (DFT) to explore the co-doping effects of single-walled carbon nanotubes (SWCNTs) with boron, aluminum, and gallium. The B3LYP functional, combined with the 6–31G(d) basis set, was applied to examine the impact of double doping effects on the electronic, optoelectronic, non-linear optical, absorption, transport, and thermodynamic properties of SWCNTs. Our results reveal that doping significantly reduces the energy gap from 2.209 eV in undoped SWCNTs to 0.967 eV, 0.975 eV, and 1.050 eV for boron, gallium, and aluminum-doped SWCNTs, respectively. Transport properties indicate that SWCNTs exhibit excellent charge transporters, with doping enhancing electron transport capacity while reducing hole transport capacity. Among the doped SWCNTs, boron-doped SWCNTs exhibited the highest reactivity. Our analysis of non-linear optical properties reveals that these materials are promising candidates for non-linear optics (NLO) and electronic applications, boasting first-order hyperpolarizability values surpassing those of urea. Absorption spectrum analysis indicates that pure SWCNTs exhibit maximum absorption in the near-ultraviolet region at 354.811 nm. After doping, a bathochromic shift occurs, resulting in absorption in the visible and infrared regions with wavelengths of 710.750 nm, 1612.056 nm, and 1643.469 nm for SWCNT/2B, SWCNT/2Al, and SWCNT/2Ga, respectively. Thermodynamic property analysis demonstrates that SWCNT/2Ga is the most thermodynamically stable, suggesting it can be synthesized effectively. These findings demonstrate that co-doping SWCNTs with boron, aluminum, and gallium not only enhances their electronic, optical, and transport properties but also establishes them as ideal candidates for advanced building technologies. Their potential applications include integration into energy-efficient photovoltaic systems, high-performance optical devices, and next-generation photonic materials. This extends to the fabrication of devices such as OLEDs, lasers, optical detectors, and optical fibers.